2016
DOI: 10.1016/j.ssresearch.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Preferences, constraints, and the process of sex segregation in college majors: A choice analysis

Abstract: The persistence of horizontal sex segregation in higher education continues to puzzle social scientists. To help resolve this puzzle, we analyze a sample of college entrants in Germany with a discrete choice design that allows for social learning from the experiences of others. We make at least two contributions to the state of research. First, we test whether essentialist gender stereotypes affect major selection mostly through internalization or rather as external constraints that high school graduates adapt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 76 publications
0
23
0
2
Order By: Relevance
“…But we can at least in part control for these potential selection processes by focusing on employment-oriented women in our sample and by considering the educational achievement and the professional position of the mothers prior to the employment interruption. Moreover, it is unclear to what extent familyrelated attitudes influence job selection in the first place (for choice in field of study e. g. Lörz and Schindler 2011;Ochsenfeld 2016). Regardless of possible selection processes, our results demonstrate that the expected improved work-family balance that female-dominated occupations promise due to higher part-time rates does not seem to be attained or does not provide sufficient incentives for the mothers to return.…”
Section: Discussion and Outlookmentioning
confidence: 65%
See 1 more Smart Citation
“…But we can at least in part control for these potential selection processes by focusing on employment-oriented women in our sample and by considering the educational achievement and the professional position of the mothers prior to the employment interruption. Moreover, it is unclear to what extent familyrelated attitudes influence job selection in the first place (for choice in field of study e. g. Lörz and Schindler 2011;Ochsenfeld 2016). Regardless of possible selection processes, our results demonstrate that the expected improved work-family balance that female-dominated occupations promise due to higher part-time rates does not seem to be attained or does not provide sufficient incentives for the mothers to return.…”
Section: Discussion and Outlookmentioning
confidence: 65%
“…For example, Hakim (2002) does not find any connection between women's preferences for family or employment and the selection of femaleor male-dominated occupations. Ochsenfeld (2016) among others finds no indication that university subject choice is determined by the anticipation of gendered family roles (see also Lörz and Schindler 2011). Additionally, research has shown that actual occupational changes in the context of starting a family are not necessarily based on the gender composition of the occupations (Trappe and Rosenfeld 2004) and that occupations dominated by women have a similar probability of being populated by women with and without children (Roos 1985).…”
Section: The Impact Of Occupational Sex Segregation On the Duration Omentioning
confidence: 99%
“…One important reason is that men choose fields of study, or college majors, that lead to more lucrative occupations in terms of income than women (e.g., Bobbitt-Zeher, 2007;Leuze & Strauß, 2009). Thus, improving our knowledge about the mechanisms behind the gendered patterns of major choices has been identified as highly relevant to combating gender inequality in the labor market (e.g., Barone, 2011;Charles & Bradley, 2002Jonsson, 1999;Legewie & DiPrete, 2014;Lörz, Schindler, & Walter, 2011;Mann & DiPrete, 2013;Morgan, Gelbgiser, & Weeden, 2013;Ochsenfeld, 2016;Zafar, 2013). In this paper, we contribute to this literature by exploring students' responsiveness to information on majorspecific wages for gender differences in major choices.…”
Section: Introductionmentioning
confidence: 99%
“…Research on gender differences in major choices (e.g., Barone, 2011;Ochsenfeld, 2016) draws on two theoretical perspectives: cultural explanations and rational choice explanations. The former state that boys and girls internalize gender stereotypes and roles during their socialization, resulting in different interests, course work patterns, (subjectively perceived) abilities, and life goals that, in turn, lead to gender differences in major choices (e.g., Charles & Bradley, 2002.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation